How the Past of Outsourcing and Offshoring is the Future of Post-Pandemic Remote Work: A Typology, a Model, and a Review - Christopher Erickson; Peter Norlander (Global Labor Organization (GLO), 2021)
Information and communication technology (ICT) challenges traditional assumptions about the capacity to manage workers beyond organizational and physical boundaries. A typology connects a variety of non-traditional work organizations made possible by ICT, including offshoring, outsourcing, remote work, virtual companies, and platforms. A model illustrates how new technology serves as a proximate cause for a revision of social contracts between capital, labor and government reached through bargaining, and how external shocks such as the COVID-19 pandemic, the institutional environment, and limitations in practice influence how technology changes the organization of work. An historical case illustrates the general features of the model, and a review of the outsourcing and offshoring literature provides instructive examples of how features of the model will potentially influence the future of post-pandemic remote work.
Keywords: J60; J50; J44; J22; O30; R12; 330; information and communication technology; institutional change; offshoring; outsourcing; remote work